Exploring the Dual Dimensions of Tehrīk-i Nifāz-i Nizām-i Muṣṭafa: An Agitational Movement for Islamic Law (Al-Qamar, 2023)
Tehrik-i Nifaz-i Nizam-i Mustafa was a bifacial movement apparently launched for the establishment of Nizam e Mustafa nonetheless targeting political objectives through agitational strategies. The paper argues that the movement was launched by the nine political parties aiming at their political ambitions under religious cover. The religious slogans employed by Pakistan National Alliance popularly known as Tehrik-i Nifaz-i Nizam-i Mustafa, were used as an agitational strategy to manipulate the religious sentiments of the common people. This agitational strategy proved successful and resulted in massive public participation in the movement that was impossible to achieve, otherwise. The research also highlights that even though the movement ended into another martial law regime in Pakistan but can be counted as successful because of its both targets achieved; to end the Bhutto government and implementation of Nizam-i Mustafa.
Keywords: Islamization; Pakistan People’s Party; Political Party, Tehrik-i Nifaz-i Nizam-i Mustafa; Z. A. Bhutto